SOCIOPSYCHOLOGICAL FORMS OF MOTIVE TO THE LABOR OF WORKERS IN THE CONTEMPORARY INDUSTRIAL ENTERPRISE - V. Levchenko (Вестник университета, 2017)
The article is realized a comparative analysis of the socio-psychological forms of motivation for work among employees of various social groups (primarily age-related), and the factors that determine them, at one of the industrial enterprises, specifies the structure of incentives, motives and needs of employees of the enterprise. Analyzed results testify to the rather high importance of the socio-psychological forms of motivation for work for the employees of the modern enterprise, and that in the structure of incentives, motives and needs of the enterprise's employees, orientation to stability and confidence, income, benefits, to a united team and good relations prevail In him, on the family, friends and close associates